Safety of Ashwagandha Root Extract: A Randomized, Placebo-Controlled, study in Healthy Volunteers. (March 2021) - Verma, Narsing; Gupta, Sandeep Kumar; Tiwari, Shashank; Mishra, Ashok Kumar
Graphical abstract: Highlights: Ashwagandha root extract was safe and tolerable for the participants. Participants' vital signs and hematological parameters were stable. Ashwagandha did not interfere with the normal liver function. Thyroid hormone levels were stable. Abstract: Background: Ashwagandha ( Withania somnifera ) is a well-established and reputed herb in Ayurvedic medicine. It has been used as a " Rasayana " (rejuvenator), nootropic, and as a powerful natural adaptogen. The herb extract is extensively used for general wellbeing and in specific ailments. However, only a few studies have investigated the safety and tolerability of Ashwagandha in humans. This study evaluated the safety of Ashwagandha root extract consumption in healthy adults. Methods: : In this randomized, double-blind, placebo-controlled, and parallel-group study, 80 healthy participants (40 males, 40 females) were randomized in a 1:1 ratio to receive either Ashwagandha 300 mg or a placebo of the same dosage, twice daily, orally for 8 weeks. The study was conducted at MV Hospital, and King George Medical University, Lucknow, India. The primary safety outcomes considered were laboratory assessment of hematological parameters, serum biochemistry analysis including hepatotoxicity evaluation, and thyroid function parameters. The secondary outcomes of this study were the clinical adverse events and the vital parameters. The within and between the groups' datasets were compared using the Wilcoxon signed-rank test and the Mann Whitney U test, respectively. Results: A detailed evaluation of the vital signs such as body weight, body temperature, pulse rate, respiratory rate, systolic and diastolic blood pressure, and Body Mass Index (BMI) were conducted for each participant at the baseline and the end of the study for treatment and placebo groups. Similarly, hematological and biochemical parameters were evaluated at the baseline and at the end of study. The outcome did not indicate any untoward effects in any of the treated volunteers. No statistically significant change or abnormality was observed in the considered parameters including thyroid hormonal profile in both the groups. No adverse events were reported by any of the participants in this study. Conclusions: Ashwagandha is being consumed since time immemorial following the Ayurvedic medicine practices. Modern science requires evidence of the safety and efficacy of the Ashwagandha extract before mass consumption for various health issues and as a supplement. The present study revealed that the consumption of Ashwagandha root extract for 8 weeks was safe in both males and females volunteers. However, long term study and varying dosage ranges should be investigated in the future.